Inquiry-based electronic student worksheets assisted with live worksheets to enhance visual-spatial - Dwi Arifianti; Kusumawati Dwiningsih (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to determine the feasibility of inquiry-based electronic student worksheets assisted with worksheets to train visual-spatial on molecular geometry topics. The 4-D development research type according to Thiagarajan, Define, Design, Develop, dan Disseminate was applied in the study. However, it was adapted into 3-D because it was only at the development stage. The results showed that the developed e-worksheets obtained 85.92% for content validity and 86.67% for construct validity with a very feasible category. The practicality of electronic worksheets in student activities was 97.98%, and student responses obtained a percentage of 93% with a very decent category. The N-Gain calculated the effectiveness of e-worksheets obtained 0.94 in the high category. The inquiry-based e-worksheets are feasible for training visual-spatial on molecular geometry materials.